Rancang Bangun Sistem Informasi Manajemen Warkah Berbasis Web di Kantor Pertanahan Kota Yogyakarta - Azriel Nauvalsyach Pinem; Harvini Wulansari (Kadaster: Journal of Land Information Technology, 2025)
Warkah management at the Yogyakarta City Land Office faces several operational constraints, including increasing physical document volume, limited storage space, and slow document retrieval. This study aims to design and develop a web-based warkah management information system to support digital document management, physical archive location tracking, and more structured archival governance. The research uses a Research and Development (R&D) approach with the Prototyping model, beginning with requirement analysis through observation and interviews, followed by rapid design, prototype construction, user feedback, and system refinement. The system is designed using Unified Modeling Language (UML) and implemented with PHP, Bootstrap, and MySQL in a Windows 11 environment. Functional validation is conducted through Black Box Testing, while system evaluation is measured using a questionnaire based on ISO/IEC 25010. The questionnaire is completed by five archival staff respondents. The results show that all functional test scenarios run as expected, and the overall evaluation score reaches 88.16%, which is categorized as very feasible. The developed system supports digital warkah storage, indexed physical archive location tracking, audit trail recording, and automatic due-date reminders. This study concludes that the developed system is feasible as an initial digital solution for supporting archival governance at the Yogyakarta City Land Office. Keywords: information system; warkah management; digital archive; prototyping; ISO/IEC 25010   INTISARI Pengelolaan warkah di Kantor Pertanahan Kota Yogyakarta menghadapi kendala berupa meningkatnya volume dokumen fisik, keterbatasan ruang penyimpanan, dan lambatnya proses pencarian berkas. Penelitian ini bertujuan merancang dan membangun sistem informasi manajemen warkah berbasis web untuk mendukung pengelolaan dokumen digital, pelacakan lokasi arsip fisik, serta tata kelola warkah yang lebih terstruktur. Penelitian ini menggunakan pendekatan Research and Development (R&D) dengan model Prototyping, dimulai dari analisis kebutuhan melalui observasi dan wawancara, perancangan cepat, pembangunan prototipe, umpan balik pengguna, hingga penyempurnaan sistem. Perancangan sistem dimodelkan menggunakan Unified Modeling Language (UML) dan diimplementasikan dengan PHP, Bootstrap, dan MySQL pada lingkungan Windows 11. Pengujian fungsional dilakukan menggunakan Black Box Testing, sedangkan evaluasi sistem diukur melalui kuesioner berbasis ISO/IEC 25010. Kuesioner diisi oleh lima orang petugas arsip. Hasil penelitian menunjukkan bahwa seluruh skenario pengujian fungsional berjalan sesuai harapan, dan nilai evaluasi sistem secara keseluruhan mencapai 88,16% yang termasuk kategori sangat layak. Sistem yang dikembangkan mendukung penyimpanan warkah digital, penelusuran lokasi arsip fisik, pencatatan audit trail, dan pengingat otomatis batas waktu pengembalian berkas. Kata Kunci: sistem informasi; manajemen warkah; arsip digital; prototyping; ISO/IEC 25010